Morfina endovenosa para analgesia de crianças submetidas a tonsilectomias: ensaio clínico - Araújo, Marcus Cavalcante de Oliveira (2017)
This dissertation was carried out in the form of two articles. The first one had the objective conduct a systematic reviewof about intravenous and intraoperative administration of morphine for the analgesia of children submitted to palatine tonsillectomy. These surgeries may have significant perioperative morbidity, with the possibility of nausea, vomiting and respiratory events such as hypoxia, especially in pediatric patients, in addition to postoperative pain, which is considered intense and can be difficult to evaluate and treat. Morphine is an opioid drug that can be used as an analgesic in these patients, but it also has the potential to lead to some of these adverse events, which makes its use infrequent in these procedures. Thus, a bibliographic review was performed in the electronic databases Pubmed, Cochrane, Lilacs, Scielo and ClinicalKey, searching for studies written in English, Portuguese or Spanish, published until June 2017. The selected uniterms were "morphine", "opioid", "analgesia", "tonsillectomy" and "tonsillectomies" and the keyword "tonsillectomy", separated by the AND and OR interlocutors. Randomized, prospective clinical trials with patients up to the age of 18 years who underwent tonsillectomy and who used intravenous morphine administered intravenously with postoperative pain evaluation were included. The research was complemented by a review of the bibliographic references of each relevant article found. In the results found, the total number of children evaluated was 1076, with physical status ASA I to III, and the postoperative pain intensity evaluation was variable, being performed through numerical pain scales (NRS), behavioral (FLACC, Hannallah, CHEOPS and modified CHEOPS), by nursing assessment in the recovery room or by simple patient complaint. Only one of the studies was placebocontrolled and eight were double-blind. Pre-anesthetic medication was administered in 6 studies and the main one was paracetamol (acetaminophen). Morphine was used as the main analgesic, with pain reduction, as well as analgesia recovery, and there were adverse effects in the postoperative period, with variable incidence of nausea, vomiting, Abstract xxi pruritus, sedation and oxygen desaturation, but without reports of gravity. The conclusion was that intravenous morphine can be successfully used to treat pain in children after tonsillectomy, despite the need for rigorous postoperative monitoring, mainly breathing, and addition of prevention of nausea and vomiting. The second article was a prospective randomized clinical trial aimed at evaluating the use of intravenous morphine for postoperative analgesia in children submitted to tonsillectomy. It includes fifty-seven children 5 to 12 years old, ASA I, submitted to elective tonsillectomy, with or without adenoidectomy, under standardized general anesthesia and distributed in two groups to receive intraoperative analgesia. One group received 0.1mg / kg morphine intravenously shortly after intubation and another group did not. Postoperative pain was assessed independently by parents / guardians and children through the Face Pain Scale at 30, 60, 120, 180 and 240 minutes. In addition, the time of awakening of the anesthesia, the need for rescue analgesics and the possible adverse effects were observed. The results showed that the group that used morphine had a lower level of pain both in the evaluation by the children, at the moment of 30 min after awakening, and by the parents / guardians, in the moments of 30, 60 and 180 minutes in relation to the other group, without increase the awakening time of anesthesia and without significant adverse effects. There was a greater need for rescue analgesics in the group that did not use morphine. The conclusion was that administration of intravenous morphine during surgery reduced the intensity of pain in the immediate postoperative period, both in the reports of the children and the parents / guardians, without increasing the time of awakening from general anesthesia or adverse effects.